Serological determination of bovine adenovirus type 1, type 2 and type 3 in cattlc in konya agricultural institution - Feridun Öztürk; Asuman Toker (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine serologically the bovine adenovirus (BAV) type 1, type 2 and type 3 infections on 214 cattle blood sera in Konya Agricultural Institution. The blood sera collected from 214 cattle were subjected to micro serum neutralization test, initially by diluting 1/10, then by diluting them two times and by comparing BAV type 1, type 2 and type 3 viruses with the ratio of 100 DKID50I 0.05 ml. Based on the results the neutralizing antibodies were found in 153 sera against BAV type 1, in 179 sera against BAV type 2 and in 191 sera against BAV type 3. These findings pointed out that the adenovirus infections which are one of the significant breeding diseases were prevalent in cattle in Konya Agricultural Institution.